Influence of support interface on the lateral performance of rocking columns in traditional Chinese timber structures. (February 2023) - Wu, Ya-Jie; Lin, He-Shou; Wang, Lei; Xie, Qi-Fang; Zhang, Li-Peng
Abstract: This study investigates the influence of support interface on the lateral performance of rocking columns in traditional Chinese timber structures. Six half-scaled timber column specimens, characterized by stone bases or timber bases, were reversed cyclically tested. Typical damage modes were identified, the load–displacement curves of the specimens were evaluated and compared with those of rigid rocking bodies. Theoretical analysis was further conducted based on a trilinear model. The experiments indicated that with the decrease of support stiffness, the damage mode of timber rocking columns shifted from slight parallel to grain deformation at column bottom to significant perpendicular to grain deformation at timber beams. The support stiffness significantly influenced the lateral performance of timber rocking columns. The peak load of a column resting on a stone base was about 80% of that of corresponding rigid rocking body, the column's hysteretic loops overlapped each other with strength degradation coefficients greater than 0.95. However, with softer timber beams as support, the peak load of a column was reduced to 46% of that of corresponding rigid rocking body, the column's hysteretic curves prominently pinched and the strength degradation coefficient decreased up to 0.1 with the increase of loading amplitude. The model-based theoretical analysis well captured the load–displacement curves of timber rocking columns on stone bases, and it further indicated when calculating the load–displacement relationship of timber rocking columns on timber beams with lower support stiffness, the local compression effect and hardening effect perpendicular to grain should be considered.